Physico-Chemical Characterization Of Silt Prepared From Bijoypur Soil (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Silt obtained from fractionated Bijoypur soil based on particle size (53~140?m) was characterized by SEM (Scanning electron microscopy), LIBS (Laser induced breakdown spectroscopy), XRD (X-Ray diffraction) and FT-IR (Fourier transform infra-red spectroscopy). pHzpc (Zero point charge pH) of silt was also determined by titrimetric method. The scanning electron micrograph of silt was taken in two different magnifications. Micrographs show that the surface of silt is slightly homogenic in nature and the particle size varied between 50 and 100 ?m. Elemental analysis of silt was performed by LIBS. According to this Fe, Si, Ti, Cu, Zn and Na are present in silt. XRD analysis indicates that silt fraction of Bijoypur soil is closely similar to kaolinite but it contains significant proportion of quartz. FT-IR analysis shows the presence of Zn=O, OH, Al-O-Si, Fe-O, Al-OH and Si-O bonds. The pHzpc value of silt was obtained as 6.39 ± 0.02 indicating neutrality of the surface. J. Asiat. Soc. Bangladesh, Sci. 39(1): 53-60, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16033